Potencial de la restauración de paisajes con especies de importancia económica para la diversificación de ingresos en la parroquia Timbara del cantón Zamora: el caso del achiote (Bixa orellana L.) - Cuenca Calva, Carmen del Rocio (2023)
Forest and landscape restoration provide the framework for implementing restorative interventions that collectively address environmental and socioeconomic challenges, to improve landscape functionality from a biodiversity conservation and production standpoint. Restorative interventions are focused on the recovery of areas that have been degraded but with the vision of obtaining benefits not only for the environment but also for society, in the sense of achieving livelihoods that contribute to improving the economy of rural households. In this context, the present research analyzes the potential of landscape restoration with economically important species such as achiote (Bixa orellana, L.) in income diversification of rural households in degraded areas. The collection of socioeconomic information on productive activities developed within the farm and other income obtained outside the farm was carried out through a survey in the parish of Timbara, Zamora canton, Zamora Chinchipe province, where active restoration projects have been implemented since 2014, with species such as achiote. Five general economic activities were identified: fish farming, agriculture, livestock, extraction of forest products, and off-farm work. In addition to these activities, households that have participated in productive restoration projects also harvest achiote fruit and contribute 1% to the economy, which is equivalent to an average of $59.30 USD per household per year. Households' acceptance to participate in future restoration projects registered a high percentage of respondents (79.3 %), of these, the desire to plant trees (95.9 %) stands out as the activity that farm owners prefer to carry out. The results obtained constitute the baseline to continue monitoring the economic impact of productive restoration and to strengthen the achiote value chain strategies in the market, as well as marketing.